EFEKTIVITAS STRATEGI PEMASARAN SOSIAL INTERNAL DAN EKSTERNAL RENCANA PEMBANGUNAN PROGRAM PLPBK DI KELURAHAN SUNGAI LAIS KECAMATAN KALIDONI KOTAMADYA PALEMBANG - Thoyib, Ellys; Effendi, R.Y. (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
Community-Based Settlement Neighborhood Setup (PLPBK) is a development programinitiated and mobilized at village/rural level in village/regency areas. This program is aNational Program, initiated by the Kementerian PUPR of through the Dirjen CiptaKarya to move the development in accordance with the needs and characteristics of thevillage / rural. Sungai Lais Village is one of 4 villages in Palembang that got thisprogram. Activity begun in 2014 begins with social mapping to determine the most slumsor priority areas, then will be built into a well-organized area of sanitation, drainage,clean water, open space and green open spaces and roads and bridges that areconnected to every area in the village. Planning Expert Team to compile developmentplan with investment value ± 7 billion, while direct aid fund (BLM PLPBK) equal to 1billion. To cover the lack of investment, Marketing Experts and citizens engage ininternal and external marketing strategy activities. Internal marketing strategy is a seriesof activities to provide understanding to the citizens about the importance of settlementarrangements well so that social and economic activities of society for the better. Citizenparticipation is not only energy and development ideas but also willingness to grant theirland affected by the development plan. Internal marketing strategy is effective enough toinfluence the citizens, because there is willingness of citizens who grant the land eventhough not all of them. An external marketing strategy is an effort to influencestakeholders' willingness to intervene in development plans that have not been financedby BLM PLPBK funds. The result of City Government through Bappeda of PalembangCity gives commitment to intervene development plan with funding scheme of RAPBDyear 2018 until 2019.